KEMIMPINAN DALAM ISLAM: STUDI TENTANG KONSEP KEMIMPINAN AL-MAWARDI DAN RELEVANSINYA DENGAN KEMIMPINAN KONTEMPORER - Safril Gazali; Zainuddin (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The purpose of this writing is to examine the study of Al-Mawardi's concept of leadership thinking and its relevance to contemporary leadership. This research method is literature study on research research and books related to Al Mawardi's thoughts. This research review below: Al Mawardi is a very productive writer and much of his work is in the form of writings in book form. One of his very popular works is Al Ahkam As Sulthaniyah Fi Al Wailaayah Ad Diniiyyah whose translation is The Laws of State Administration in Islamic Sharia. This study analyzes Imam Al Mawardi's thoughts in the contemporary context by paying attention to the opinions of related figures. The results of this study of Tooh's thinking reveal that Imam Al Rosedi still considers the people to have the right to impeach leaders who are deemed no longer worthy of being leaders even in a monarchical government